Studi Kasus Pengambilan Keputusan Mahasiswa Calon Guru Matematika dalam Merencanakan Penjelasan Instruksional - Hadi, Syaiful; Nadya Alvi Rahma (Jurnal Riset Pembelajaran Matematika, 2025)
This research aims to analyze the role of prospective mathematics teacher students in planning actions according to the components of decision-making in the context of classroom learning. The type of research carried out was a case study with the research subjects being prospective mathematics teacher students from the Tadris Mathematics Study Program, Sayyid Ali Rahmatullah State Islamic University Tulungagung, who were carrying out internship courses in the education unit at SMPN 1 Sumber Gempol Tulungagung. In planning the action, the subject involves three main processes in providing an instructional explanation of straight-line equation material. In idea-generation activities, the subject collects information in the form of relevant ideas for developing alternatives. In clarifying ideas, the subject analyzes the ideas by breaking down the information into categories for each main idea produced. Ideas regarding students' ability to master concepts, for example, are divided into initial and new concepts, and then grouped into high, medium, and low ability categories. In assessing the reasonableness of an idea, the subject analyzes and evaluates the various idea information generated, then synthesizes it to decide on selecting actions to achieve goals. In this process, the subject focuses on two sub-materials to study: the drawing process and constructing formulas.